Examining the Impact of WRITE Learning Model on Students' Critical Reading Skill in Elementary School - Handara Tri Elitasari; Zamzani Zamzani; Mami Hajaroh (Jurnal Penelitian Ilmu Pendidikan, 2026)
Despite the recognized importance of critical reading for academic success, elementary school students in Indonesia continue to demonstrate low proficiency in this skill, particularly in connecting texts with personal experiences and evaluating information critically. This gap is exacerbated by the limited integration of technology-based literacy models that simultaneously develop reading and writing competencies. This study aims to analyze the influence of WRITE (Writing-Reading Literacy Assisted Interactive and Reflective E-Book) learning models on critical reading skills of elementary school students. This study uses a quantitative method with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to analyze the relationship between the tested variables. The research instrument used questionnaires to measure various aspects of critical reading skills. The sample used in this study amounted to 71 students from elementary school in Magelang. The results showed that most of the hypotheses tested had significant relationships, especially in the aspects of analysis, interpretation, evaluation, and inference that affected students' critical reading skills. However, some factors such as appreciation of critical reading skills did not show significant influence. The learning model in this study has been proven to be effective in improving students' critical reading skills. This research contributes to the development of technology-based learning methods that can be implemented in elementary education to improve students' critical thinking skills.